On the fredholm theory of a planar problem with shift for a pair of functions - Lysenko, Z. M.; Matviyuk, L. V.; Nechaev, L. V.; Shvets, V. T. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain necessary and sufficient conditions of the Fredholm properties and the formula for the calculation of index of a planar problem with shift and conjugation for a pair of functions.